2023
DOI: 10.1155/2023/1073984
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Immune Imbalance is an Alarm in the Development of IBD

Chunli Hu,
Shengtao Liao,
Lin Lv
et al.

Abstract: Immune regulation plays a crucial role in human health and disease. Inflammatory bowel disease (IBD) is a chronic relapse bowel disease with an increasing incidence worldwide. Clinical treatments for IBD are limited and inefficient. However, the pathogenesis of immune-mediated IBD remains unclear. This review describes the activation of innate and adaptive immune functions by intestinal immune cells to regulate intestinal immune balance and maintain intestinal mucosal integrity. Changes in susceptible genes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 246 publications
0
4
0
Order By: Relevance
“…IBD benefits from resveratrol's therapeutic effects. In both Crohn's disease (CD) and ulcerative colitis (UC), it reduces pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and restores the balance between Tregs and Th17 cells [103,104]. Furthermore, resveratrol demonstrates a neuroprotective role in vitro and in vivo, showcasing its potential in tackling neurodegenerative diseases.…”
Section: Targeting Inflammation Using Natural Compoundsmentioning
confidence: 99%
“…IBD benefits from resveratrol's therapeutic effects. In both Crohn's disease (CD) and ulcerative colitis (UC), it reduces pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) and restores the balance between Tregs and Th17 cells [103,104]. Furthermore, resveratrol demonstrates a neuroprotective role in vitro and in vivo, showcasing its potential in tackling neurodegenerative diseases.…”
Section: Targeting Inflammation Using Natural Compoundsmentioning
confidence: 99%
“…Similar to IgAN with unclear etiology and pathogenesis, IBD is a troublesome heterogeneous disease with an unignorable influence on millions of people worldwide [ 11–13 ]. A genome-wide study revealed that a multitude of loci associated with IgAN were related to immune-mediated IBD, intestinal barrier preservation, and gut pathogens reactions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…IBD is an uncontrolled inflammatory condition of the gastrointestinal tract, which mainly manifests in two forms: ulcerative colitis (UC) and Crohn's disease (CD), both of which are characterized by chronic inflammation in the gastrointestinal tract and repeated cycles of relapse and remission. The pathogenesis of IBD appears to be associated with abnormal gut microbiota, environmental changes, gene variants, and immune response dysregulation [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%